1987
DOI: 10.1056/nejm198710013171403
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol in the Prevention of First Upper Gastrointestinal Tract Hemorrhage in Patients with Cirrhosis of the Liver and Esophageal Varices

Abstract: We conducted a prospective, randomized, multicenter, single-blind trial of propranolol as compared with placebo in the prevention of first upper gastrointestinal tract bleeding in patients with cirrhosis of the liver. A total of 230 patients (90 percent with alcoholism and 46 percent with a Child-Pugh grade C classification) with large esophageal varices without previous bleeding were randomly assigned to receive either propranolol (n = 118) or placebo (n = 112), after they had been divided into two groups acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(100 citation statements)
references
References 35 publications
2
96
0
2
Order By: Relevance
“…This reduction is smaller than the range of 20 to 26 percent (median, 24 percent) reported in studies of beta-blockers in the primary prophylaxis of variceal hemorrhage [16][17][18][19][20][21][22][23][24] and is probably due to the lower baseline heart rate (median, 73 beats per minute) in our study than in primary-prophylaxis studies of patients with varices (median, 80 beats per minute) 9,17-25 or secondaryprophylaxis studies of patients with varices (median, 84 beats per minute). [26][27][28][29] However, the absolute heart rate achieved is a better indicator of betablockade than the percent reduction in heart rate, 30 and the absolute heart rate in our study during timolol therapy (62 beats per minute) was similar discussion to the median heart rate of 60 beats per minute among patients receiving beta-blockers in previous studies.…”
Section: Hemodynamicsmentioning
confidence: 56%
“…This reduction is smaller than the range of 20 to 26 percent (median, 24 percent) reported in studies of beta-blockers in the primary prophylaxis of variceal hemorrhage [16][17][18][19][20][21][22][23][24] and is probably due to the lower baseline heart rate (median, 73 beats per minute) in our study than in primary-prophylaxis studies of patients with varices (median, 80 beats per minute) 9,17-25 or secondaryprophylaxis studies of patients with varices (median, 84 beats per minute). [26][27][28][29] However, the absolute heart rate achieved is a better indicator of betablockade than the percent reduction in heart rate, 30 and the absolute heart rate in our study during timolol therapy (62 beats per minute) was similar discussion to the median heart rate of 60 beats per minute among patients receiving beta-blockers in previous studies.…”
Section: Hemodynamicsmentioning
confidence: 56%
“…Similarly, these agents are used to treat extra-cardiac diseases such as migraine and glaucoma [7] , and in the 1980s they were introduced in the treatment of variceal hemorrhage in patients with cirrhosis and portal hypertension [8][9][10][11] .…”
Section: Beta-blockersmentioning
confidence: 99%
“…[3][4][5][6] Several randomized controlled trials have demonstrated that the use of nonselective beta-adrenergic blockers (propranolol, nadolol) in patients at high risk for bleeding reduces the risk itself (by about 45%) [7][8][9][10] and tends to reduce the mortality rate. 11 Use of propranolol has resulted in a lower rate of bleeding when compared with sclerotherapy in one study 6 and a better survival time in another. 12 In most studies, recurrent bleeding is effectively prevented by administration of beta-blockers alone or in association with sclerotherapy.…”
mentioning
confidence: 99%
“…11,15,-17 Two recent studies singled out the sequential measurement of the HPVG as the only parameter capable of predicting a reduction in the risk of first or recurrent bleeding in treated patients. A marked reduction in the occurrence of bleeding is guaranteed if the administration of the drug reduces the HPVG to below 12 mm Hg 11 or by more than 20% 12 after a period of treatment. This approach is fundamental because it can indicate the need for second-line treatment; however, owing to its being a complex and invasive technique, it has not found favor with clinicians.…”
mentioning
confidence: 99%